2011
DOI: 10.1002/anie.201101009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isoquinolines from α‐Aryl Vinyl Azides and Internal Alkynes by Rh–Cu Bimetallic Cooperation

Abstract: Catalysts in a relay: A synthetic method for delivering highly substituted isoquinolines has been developed (see scheme; Cp*=C5Me5, DMF=N,N‐dimethylformamide, TEMPO=2,2,6,6‐tetramethylpiperidine‐1‐oxyl). A preliminary mechanistic study showed that the rhodium and copper cooperate synergistically in the multistep sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(64 citation statements)
references
References 56 publications
1
58
0
2
Order By: Relevance
“…2 H -Azirines have been reported as intermediates in reactions involving vinyl azides as a result of the denitrogenative decomposition of the latter via vinyl nitrenes4748. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 H -Azirines have been reported as intermediates in reactions involving vinyl azides as a result of the denitrogenative decomposition of the latter via vinyl nitrenes4748. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 Preliminary mechanistic investigations indicated that both rhodium and copper are prerequisites for achieving catalytic activity. It was also found that benzylic radical intermediates were trapped by 2,6-di-tert-butyl-4-methylphenol (TEMPO), when it was added instead of HOAc (Scheme 12).…”
Section: Transition Metal-catalyzed Reactions Of Vinyl Azidesmentioning
confidence: 99%
“…c). 5 In the syntheses of N -heterocycles, a radical pathway might also be involved, in which α -azido radicals, 8 , generated from radical species (R · ), add to vinyl azides, to produce iminyl radicals, 9 (Scheme 1, eq. d).…”
Section: Introductionmentioning
confidence: 99%
“…48 While the use of sodium acetate (NaOAc) or cesium pivalate (CsOPiv) (30 mol%) as a carboxylate source did not afford any ortho carbon-hydrogen bond functionalization product (entries 1 and 2, respectively), the reaction with copper(II) acetate [Cu(OAc) 2 ] (20 mol%) at 110 °C in N,N-dimethylformamide (DMF) gave 1-methyl-3,4-diphenylisoquinoline (237) in 70% yield (entry 3). The addition of 1 equivalent of AcOH allowed for a lower reaction temperature (90 °C) and catalytic loading of [Cp*RhCl 2 ] 2 (2.5 mol%) (entries 5 and 6).…”
mentioning
confidence: 97%
“…After the extensive screening of various electrophiles, it was found that the addition of TEMPO (2,2,6,6-tetramethylpiperidin-1-yloxyl) (2 equiv) instead of AcOH in the reaction of vinyl azides 62 and 277 with several alkynes under the [Cp*RhCl 2 ] 2 -Cu(OAc) 2 catalytic system delivered isoquinoline-TEMPO adducts and alcohols in good combined yields (Table 14). 48,52 From vinyl azide 277, a b-amino alcohol unit could be installed in the isoquinoline framework (entry 4). Although we are not certain as to the reaction mechanism of this carbonoxygen bond formation, one possibility might be the nucleophilic attack of the azaenolate carbon to a Cu(II)-TEMPO complex, which would act as an ionic electrophile.…”
mentioning
confidence: 99%